Induced pluripotent stem cells reduce neutrophil chemotaxis via activating GRK2 in endotoxin‐induced acute lung injury. Issue 6 (21st April 2017) - Su, Vincent Yi‐Fong; Chiou, Shih‐Hwa; Lin, Chi‐Shiuan; Chen, Wei‐Chih; Yu, Wen‐Kuang; Chen, Yen‐Wen; Chen, Cheng‐Yu; Yang, Kuang‐Yao
ABSTRACT: Background and objective: We investigated the effect of induced pluripotent stem cells (iPSCs) in moderating neutrophil chemotaxis in endotoxin‐induced acute lung injury (ALI). Methods: Male C57BL/6 mice at 8–12 weeks of age were studied. Murine iPSCs were delivered through the tail veins of mice 4 h after intratracheal instillation of endotoxin. Lung histopathological findings, neutrophil counts in peripheral blood and bronchoalveolar lavage fluid (BALF), bone marrow (BM) cell distribution, expression of chemokine receptors and regulatory signalling pathways were analysed after 24 h. Human neutrophils isolated from acute respiratory distress syndrome patients were used in a cell migration assay. Results: iPSCs significantly decreased the histopathological changes of ALI in mice compared to treatment with control cells. Numbers and activity levels of neutrophils in BALF were reduced in iPSC‐treated ALI mice. The iPSC therapy restored neutrophil counts in the peripheral blood of ALI mice, but the percentages of mature neutrophils in BM were similar between iPSC‐treated and ‐untreated groups. The iPSCs mediated a downregulation of the chemotactic response to endotoxin by reducing chemokine (C‐X‐C motif) receptor 2 (CXCR2) expression on mouse peripheral blood neutrophils. This result was confirmed by an in vitro human neutrophil migration assay. In addition, iPSCs or conditioned medium from iPSCs enhanced expression of G protein‐coupled receptor kinase 2 (GRK2) on the surface of blood neutrophils in ALI mice. Conclusion: iPSCs reduce neutrophil chemotaxis in endotoxin‐induced ALI. These effects are associated with an enhancement of GRK2 activity and reduction of CXCR2 expression. Abstract : This study showed that induced pluripotent stem cells downregulate neutrophil chemotaxis in endotoxin‐induced acute lung injury, an effect associated with enhancement of G protein‐coupled receptor kinase 2 (GRK2) activity and reduction of chemokine (C‐X‐C motif) receptor 2 (CXCR2) expression.